An analysis of income inequality, social security and competitiveness : an essay on Dr Goh Keng Swee's contributions to Singapore's economic strategy - Chew, Soon Beng (2013)
Dr Goh Keng Swee has been credited as being the social and economic architect of Singapore. In his 25 years of government service, he served in a wide range of ministerial appointments, including Deputy Prime Minister, Minister of Finance, Minister of Defence and Minister of Education. This paper discusses a specific aspect of his contributions to Singapore's economic strategy, namely that of reducing income inequality without compromising competitiveness.